2018
DOI: 10.1111/1759-7714.12929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of ≥ 50% PD‐L1 expression with the SP263 monoclonal antibody in non‐small cell lung cancer patients

Abstract: Background PD‐L1 expression in tumor cells has been associated with the efficacy of immune checkpoint inhibitors in non‐small cell lung cancer (NSCLC). The aim of this study was to explore correlations between smoking, genetic profiles, patient outcomes, and PD‐L1 expression in NSCLC. Methods PD‐L1 expression was evaluated in 241 surgically resected specimens by immunostaining and 50% was set as the cutoff value. Results Of the 241 tumors ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This finding is in consistent with previous analysis in European and American cohorts [5, 26, 29]. Other studies reported lower PD-L1 positivity using antibody clone 28–8 (overall 31% in NSCLC, ≥1% cutoff) [30] and clone SP263 (overall 36.5% in NSCLC, ≥1% cutoff) [31]. The positive rates are even lower as measured by another PD-L1 antibody, clone 22C3 (4.4% any+ in ADC and 34.3% any+ in SQCC) [32].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in consistent with previous analysis in European and American cohorts [5, 26, 29]. Other studies reported lower PD-L1 positivity using antibody clone 28–8 (overall 31% in NSCLC, ≥1% cutoff) [30] and clone SP263 (overall 36.5% in NSCLC, ≥1% cutoff) [31]. The positive rates are even lower as measured by another PD-L1 antibody, clone 22C3 (4.4% any+ in ADC and 34.3% any+ in SQCC) [32].…”
Section: Discussionsupporting
confidence: 91%